Strategic foresight and utilization of future-oriented information in Finnish SMEs – Reframing the intermediary role of Tekes - Pouru, Laura (My University, 2016)
The economic importance of small and medium-sized enterprises (SMEs) has been increasingly recognized in Finland during recent years. In order to succeed in the turbulent global markets SMEs need competence to utilize future-oriented information in creating agility to adapt to the changing business environment. However, there is very little research done on strategic foresight in SMEs while most of corporate foresight research has been done in the context of large companies. This thesis addresses the issue of strategic foresight in SMEs. The focus of the thesis is to study how foresight is practiced and future-oriented information utilized in Finnish SMEs. Furthermore, the information intermediary role of Tekes (The Finnish Funding Agency for Innovation) is reformulated in the thesis. The theoretical basis of the thesis is built on theories and approaches of strategic foresight, utilization of externally produced future-oriented information and knowledge broker role of intermediary organizations. The solution-oriented design research approach of the thesis narrows the empirical focus group of the research down to the SMEs that currently receive innovation funding from Tekes. Empirical material of the research consists of survey responses from 101 SMEs. The research material was collected with a Webropol-based survey in May-June 2016. Results of the research indicate that SMEs are active in their foresight practices and majority of the respondent SMEs are utilizing several foresight methods. However, SMEs have a strong tendency to rely heavily on their immediate business environment when looking for future-oriented information. Future-oriented information is regarded most important in strategic planning and renewing of the product portfolio. The results also indicate that SMEs have relatively mature foundations for strategic foresight built on cultural foundations, e.g. in majority of the SMEs employees are encouraged to think big and bring in new ideas. The results also show that SMEs are not very familiar in utilizing current foresight services of Tekes. Therefore, a coaching-based constructivist foresight framework that emphasizes the role of Tekes as a “futures facilitator” supporting the endogenous foresight competencies of SMEs is outlined as the outcome of the research. The suggested framework is built on three principal functions: 1) disseminating future-oriented information from the periphery where SMEs don’t scan with their information scanning radars, 2) providing support and tools for the analysis of future-oriented information, and 3) encouraging future-oriented thinking in SMEs through coaching sessions.